Effect of Selenophene in a DPP Copolymer Incorporating a Vinyl Group for High‐Performance Organic Field‐Effect Transistors. (2nd November 2012) - Kang, Il; An, Tae Kyu; Hong, Jung‐a; Yun, Hui‐Jun; Kim, Ran; Chung, Dae Sung; Park, Chan Eon; Kim, Yun‐Hi; Kwon, Soon‐Ki
<x xml:space="preserve">Abstract</x> A new polymeric semiconductor, PDPPDTSE, is reported which is composed of a diketopyrrolopyrrole moiety and selenophenylene vinylene selenophene, with a high field‐effect mobility achieved through intermolecular donor–acceptor interactions. The field‐effect mobility of OFET devices based on PDPPDTSE by spin‐casting is 4.97 cm2 V−1 s−1, which is higher than predecessor polymeric semiconductors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>